An unusual diagnosis for an usual test - Andrea Trombetta; Vanessa Migliarino; Flavio Faletra; Egidio Barbi; Gianluca Tornese (BMC, 2020)
Abstract Background Hereditary multiple osteochondromas (HMO) is a genetic condition characterized by the presence of multiple osteochondromas, usually at the lateral side of the most active growth plate of a long bone. These lesions may persist, be asymptomatic during childhood, and may increase in number and size until growth plates close. Therefore, diagnosis of HMO in children and young people can be challenging; while short stature can be more evident at the onset of puberty, asymptomatic ostheocondromas can progress into different degrees of orthopedic deformity. Moreover, multiple complications may arise due to the presence of osteochondromas, including tendon and compression muscle pain, neurovascular disorders, obstetric problems, scoliosis and malignant transformation into secondary peripheral chondrosarcoma in adulthood. Case presentation We report the case of a girl admitted to our Institute for growth delay. While laboratory tests, including growth hormone stimulation test, were normal, left hand X-ray revealed multiple osteochondromas, suggestive for HMO. The genetic test for EXT1 and EXT2 genes confirmed the radiological diagnosis, with a mutation inherited from the mother who displayed the same radiological abnormalities along with recurrent limb pain episodes. Conclusions HMO is a genetic condition whose diagnosis can be challenging, especially in females. Every pediatricians should consider a skeletal dysplasia in case of unexplained growth delay and a skeletal survey might be fundamental in reaching a diagnosis.